SEJARAH PENDIDIKAN ISLAM DI REJANG LEBONG - Adeka Fajar; Aditya Gusti Pratama; Ahmad Annizar; Ahmad Pajar Prasetiyo; Depri Aresa; Deki Perliansyah; Deni -; Fadel Muhamad; Ilham Sahbandi; Siswanto Siswanto (Ta'dib (Jurnal Ilmiah Pendidikan dan Peradaban Islam), 2020)
Education is one of the learning methods provided by educators to students, be it formal or non-formal education. The history of education in rejang lebong is certainly inseparable from the community in it and is supported by the existence of available educational institutions, such as madrasahs, islamic boarding schools or Islamic universities. The entry of Islam in Rejang Lebong occurred before the 17th century, namely before the biksus came to Rejang Lebong to broadcast Hinduism/Buddhism. The center of Islamic teachings in Rejang Lebong is located in Sawah Hamlet, where at that time the Sawah Hamlet area was referred to as a small Mecca. So called because at that time Sawah Hamlet became a religious center, when someone was going to take the Hajj, then the center of their association before leaving, namely in Sawah Hamlet. The purpose of this study was to find out how Islam and Islamic education in the land of Rejang, as for the method used, namely the historical method is to help to obtain research results in the form of systematic and objective reconstruction of the past at an understandable level.